The Level of Participation Among Non-English Major Students in English Classroom Activities - Helena Tada; Chairil Anwar Korompot; Geminastiti Sakkir (GLENS: Global English Insights Journal, 2025)
This study investigates the level of classroom participation among non-English major students enrolled in English language courses. Employing a quantitative descriptive approach, data were collected through a structured questionnaire distributed to 20 randomly selected first-semester students from the Faculty of Sports and Health Sciences at Universitas Negeri Makassar. The results indicate that 80% of the participants demonstrated active (65%) or very active (15%) involvement in classroom activities, while 20% remained neutral. No students were categorized as passive. The mean participation score of 50 falls within the "active" category. Further analysis shows that students are more engaged in interactive activities such as asking questions (65%), expressing opinions (50%), and participating in discussions (60%). In contrast, passive indicators like sitting quietly or merely listening were less frequently reported. While 45% of students stated they mainly took notes, another 45% were unsure whether they only took notes or also engaged in discussion. These findings suggest that, despite not majoring in English, students exhibit a high level of participation in English classroom activities. This highlights the potential of incorporating interactive strategies to further enhance engagement in English as a Foreign Language (EFL) instruction.